UREA HIGH TEMPERATURE GREASE FOR AIRCRAFT - Zheleznyi, Leonid; Veligorska, Iuliia; Venger, Irina; Papeikin, Oleksii (Proceedings of National Aviation University (archive), 2017)
Purpose: The research results of the synthesis of multipurpose urea grease are based on synthetic oils for use in a wide temperature range, suitable for use in aviation engineering. Methods: The interaction of polyisocyanate with octadecylamine and benzylamine in a mixture of polyalphaolefin oil with pentaerythritol esters and fatty acids of the C5-C9 fraction was synthesized polyurea – thickener of urea greases. Its structure was established by IR spectroscopy. The method of derivational analysis was used to determine the upper temperature limit of grease application. The properties of grease are investigated by standard methods. Results: IR spectra of urea grease indicate that was applied for the synthesis of the thickener the ratio of reagents, leads to their full consumption during the reaction and allows to obtain urea with the maximum output. The nature of the curves of differential thermal analysis and thermogravimetry indicates that the upper temperature limit for the application of urea grease made on a mixture of synthetic oils is at 200 °C. It is established that the synthesis temperature and the ratio of the components of the thickener determine the thermal, rheological and mechanical properties of the system. By varying the molar ratio of the components of the urea thickener, it was possible to create a mechanical and colloidal stable lubricanting composition. The grease does not freeze to minus 50 °C, which is confirmed by the low viscosity at this temperature and the value the starting and the running torque of rotation of bearing. Applications of a multifunctional additive package allowed to enter a new qualitative level of tribological characteristics and resistance to oxidative conversions. Discussion: Researches shown that the properties of urea grease depend on not only on the nature and the ratio of the components of the urea thickener and the parameters of the process of its synthesis, but also on the balance of the lubricating composition as a whole with properly selected base oils and an additive package. The developed product with a high level of tribological, antioxidant and ecological characteristics meets the modern requirements for aviation greases and can be recommended for using in harsh operating conditions over a wide temperature range.